Effects of exogenous salicylic acid on the adaptive capacity of Leymus chinensis seedlings under extreme drought conditions - Li, Chongyang; Liu, Xinying; Li, Bin; Yang, Rong; Hou, Xiangyang (Frontiers in Plant Science, 2025)
To investigate the effects of exogenous salicylic acid (SA) on the growth characteristics of Leymus chinensis seedlings under extreme drought stress, this study utilized L. chinensis seedlings as experimental materials and simulated drought conditions using a rainout shelter to exclude natural precipitation. SA solutions at six concentrations (0, 0.25, 0.50, 1.00, 2.00, and 4.00 mmol/L) were applied via foliar spraying. Key growth parameters, photosynthetic traits, chlorophyll fluorescence indices, osmotic adjustment substances, and antioxidant enzyme activities were systematically measured and analyzed. The results showed that exogenous SA significantly alleviated the suppression of seedling height growth caused by extreme drought stress. Under drought conditions, plants treated with 0.50 mmol/L SA exhibited peak levels of chlorophyll (Chl) and proline (Pro) content, both of which were significantly higher than those in the control group (P < 0.05). Additionally, this treatment increased leaf relative water content, soluble sugar (SS) accumulation, superoxide dismutase (SOD) activity, and catalase (CAT) activity compared to the control. Notably, stomatal conductance (gs) was minimized in the 0.50 mmol/L treatment under drought stress, indicating reduced transpirational water loss and improved water-use efficiency. Overall, exogenous SA enhanced the photosynthetic performance, antioxidant defense capacity, and osmotic regulation ability of L. chinensis seedlings. These findings demonstrate that application of 0.50 mmol/L SA effectively mitigates the detrimental effects of extreme drought stress, improves drought tolerance in L. chinensis seedlings, and holds promise for enhancing the resilience and sustainability of grassland ecosystems under increasingly severe drought conditions.